Estimating the Parameters of Laser Processing of Diamonds Using the Finite Element Method and Artificial Neural Networks - V. A. Emelyanov; E. B. Shershnev; Yu. V. Nikitjuk; S. I. Sokolov; I. Y. Aushev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
This paper provides the simulation of laser processing of diamonds by using a combination of artificial neural networks and the finite element method. The training data array and the data array for testing neural networks were generated in ANSYS. The calculations were performed for 600 types of input parameters, 60 of which were used to test artificial neural networks. The influence of the parameters of neural network models on the accuracy of determining temperatures in the laser processing area were studied. The parameters of neural networks were established that provide acceptable results in predicting temperatures generated by laser radiation in diamonds. The results obtained can be used to determine the technological parameters of the laser processing of diamonds.